Natural course and risk factors of moyamoya disease with unruptured intracranial aneurysm - Yang, Ri-Miao; Hao, Fang-Bin; Zhao, Bo; Zhang, Qian; Yu, Dan; Zou, Zheng-Xing; Gao, Gan; Guo, Qing-Bao; Shen, Xu-Xuan; Fu, He-Guan; Liu, Si-Meng; Wang, Min-Jie; et al. (Frontiers in Neurology, 2023)
Background and objective The natural course and risk factors of moyamoya disease (MMD) associated with unruptured intracranial aneurysms involving stenosed parental arteries are scarcely studied. This study aimed to elucidate the natural course of MMD and its associated risk factors in patients with MMD with unruptured aneurysms. Methods Between September 2006 and October 2021, patients with MMD with intracranial aneurysms at our center were examined. The natural course, clinical features, radiological features, and follow-up outcomes after revascularization were analyzed. Results This study included 42 patients with MMD with intracranial aneurysms (42 aneurysms). The age distribution of MMD cases ranged from 6 to 69 years, with four children (9.5%) and 38 adults (90.5%). A total of 17 male and 25 female subjects were included (male-to-female ratio: 1:1.47). The first symptom was cerebral ischemia in 28 cases, and cerebral hemorrhage occurred in 14 cases. There were 35 trunk aneurysms and seven peripheral aneurysms. There were 34 small aneurysms (<5 mm) and eight medium aneurysms (5–15 mm). During the average clinical follow-up period of 37.90 ± 32.53 months, there was no rupture or bleeding from aneurysms. Twenty-seven of these patients underwent a cerebral angiography review, in which it was found that one aneurysm had enlarged, 16 had remained unchanged, and 10 had shrunk or disappeared. A correlation exists between the reduction or disappearance of aneurysms and the progression of the Suzuki stages of MMD (P = 0.015). Nineteen patients underwent EDAS on the aneurysm side, and nine aneurysms disappeared, while eight patients did not undergo EDAS on the aneurysm side and one aneurysm disappeared. Conclusion The risk of rupture and hemorrhage of unruptured intracranial aneurysms is low when the parent artery already has stenotic lesions, thus, direct intervention may not be necessary for such aneurysms. The progression of the Suzuki stage of moyamoya disease may play a role in the shrinkage or disappearance of the aneurysms, thereby decreasing the risk of rupture and hemorrhage. Encephaloduroarteriosynangiosis (EDAS) surgery may also help promote atrophy or even the disappearance of the aneurysm, thus reducing the risk of further rupture and bleeding.